Investigation of Provision of Services to Students of Determination in the Federal Higher Education Institute in the UAE - NADEEM, FARHANA (2020)
The focus of this research is to present the challenges encountered by the Students of Determination (as known here in UAE) and their current level of satisfaction in utilizing the provisions offered by the Federal University of the UAE, on its campuses in Dubai and Abu Dhabi. The study also shows the barriers encountered by the Faculty and the Specialists in the Accessibility Unit in providing the interventions needed by the Students of Determination. The researcher used Bronfenbrenner’s Bio-ecological framework and an explanatory sequential mixed method design for this research. The data collection was done between 2019 May and June 2020. Quantitative data were collected through surveys and qualitative data was gathered through semi-structured interviews. The data was collected from Students of Determination themselves, Faculty members and Specialists of seven colleges of the Federal Higher Education University. Each campus has Student Accessibility Services Unit (SAS) offering support services to students with Specific Learning Disabilities, Visual Impairment, Hearing Impairment, Attention Deficit Hyperactive Disorder and Physical Impairment. In the analysis of quantitative data, t-test, was conducted to examine the differences between the mean score. Qualitative data from interviews and focus group was analyzed using thematic analysis. From the findings of this research the following recommendations have been made. Training is needed for the Faculty to be equipped with strategies to cater to diverse needs. Students of Determination coming from government schools have a low level of English as the medium of instruction is Arabic. The Foundation Course is short to make the students proficient in accessing Higher Education courses in the English Language. The number of personnel in the Accessibility Unit needs to be increased. This study recognizes the need for clear Inclusive Education Policies in Higher Education to realize the goal of “Education for All”. To improve the transition procedure from the Secondary to the Higher Education needs to be smooth. It is imperative for Students of Determination to be equipped with a positive self-concept, self-advocacy and social skills at the secondary level. The findings of this research will be useful to the higher education institutes to improve the quality of inclusive practices.